Annual Cluster Conference "Spatialities": Book Conversation (Conference Spatilities 2023, 2024)
As part of the Cluster's Annual Conference on "Spatialities" Christine Vogt-Williams and Epifania Amoo-Adare talked about Amoo-Adare's book "Spatial Literacy - Contemporary Asante Women's Place-Making". A central premise informing the concept of Critical Spatial Literacy is the decryption of specific codes found in the built environment so as to understand how these affect people’s social lives, cultural practices and sense of place. The conversation addresses how Critical Spatial Literacy might work as a conceptual frame to explore how the social and economic lives of women of (continental and diasporic) African descent have been constituted, situated and enacted in contemporary spatialities. One salient point concerns how the concept might allow for African feminist and womanist responses to uneven development. Epifania Amoo-Adare is an independent scholar, who is interested in (un)thinking science through art and other radical approaches. She is currently based in Accra, where she is seeding Biraa Creative Initiative (BCI). Epifania has a Ph.D. in Education from UCLA and is a RIBA Part II qualified architect. Born in London, and raised in Nairobi, Cape Coast and Accra, Epifania also has over 25 years of experience working in various flelds, including education and international development, within locations like Afghanistan, Georgia, Germany, Ghana, Qatar, the United Kingdom and the United States. Her post-disciplinary interests span diverse topics such as creative writing, critical pedagogy, decolonial thinking, epistemology, feminism(s), spirituality, spatial theories, and urbanization.